2020
DOI: 10.1016/j.isci.2020.101175
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Injury Does Not Stimulate Striatal Neuron Replacement Even during Periods of Active Striatal Neurogenesis

Abstract: Phenotyping of thousands of cells generated after striatal ischemic injury Confirms previous reports on lack of injury-induced adult striatal neurogenesisNo ''self-repair'' even during active periods of neonatal striatal neurogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Immunohistochemistry was performed on free-floating sections as previously described [ 54 ]. Primary antibodies specific for NeuN (1:500; Abcam, ab104225, Cambridge, MA, USA) or Iba1 (1:1000; Wako, West Grove, PA, USA, 019-19741) were incubated overnight to detect neurons or microglial, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed on free-floating sections as previously described [ 54 ]. Primary antibodies specific for NeuN (1:500; Abcam, ab104225, Cambridge, MA, USA) or Iba1 (1:1000; Wako, West Grove, PA, USA, 019-19741) were incubated overnight to detect neurons or microglial, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…One area where birthdating studies using BrdU have been fundamentally important is in our understanding of the proliferative response following brain injury, for example after modeling of stroke in rodents ( Ermine et al., 2020 ). These studies are built around a ‘pulse-chase’ design, where BrdU is delivered systemically to animals to birthdate dividing cells during a defined ‘pulse’ period, followed by a ‘chase’ period that allows the labeled cells time to differentiate in order to facilitate immunohistochemical phenotyping based on the expression of mature markers of cellular identity.…”
Section: Before You Beginmentioning
confidence: 99%
“…Previous studies in rodents have shown that intraperitoneal (i.p.) injection of BrdU at a dose of 50 mg/kg every 12 h is sufficient to label all dividing cells in the neurogenic subventricular zone ( Arvidsson et al., 2002 ) although 100 mg/kg is also commonly used ( Ermine et al 2020 ). The appropriate chase period should be determined based on the aim of the experiment.…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations